2012
DOI: 10.4236/wjcd.2012.21003
|View full text |Cite
|
Sign up to set email alerts
|

The effects of EPA + DHA and aspirin on inflammatory cytokines and angiogenesis factors

Abstract: Objective In a recent study, we showed that the combination of aspirin plus the omega-3 fatty acids eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) synergistically inhibited platelet function. As aspirin, EPA, and DHA have demonstrated anti-inflammatory properties, we hypothesized that the ingestion of EPA and DHA, with and without aspirin, would reduce plasma levels of inflammatory cytokines and angiogenesis factors more than aspirin alone and before aspirin was ingested. Methods Using multiplex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 21 publications
3
23
0
Order By: Relevance
“…We utilized a well-validated technology to measure the 78 markers of inflammation and used a novel two-stage design that allowed for the reweighting of the analysis to the population-based PLCO screening arm. While we did not observe significant associations, our results are in agreement with previous studies in similar populations (9, 11, 14, 16, 31). …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We utilized a well-validated technology to measure the 78 markers of inflammation and used a novel two-stage design that allowed for the reweighting of the analysis to the population-based PLCO screening arm. While we did not observe significant associations, our results are in agreement with previous studies in similar populations (9, 11, 14, 16, 31). …”
Section: Discussionsupporting
confidence: 92%
“…: chronic heart disease and metabolic syndrome) (7, 9-13, 15). As with this current analysis, previous studies conducted in healthy populations have consistently failed to show an association between aspirin use and any of the inflammatory markers examined in the studies (9, 11, 14, 16, 31). Individuals with chronic inflammation may be physiologically different than healthy individuals and would be expected to have higher baseline levels of inflammation, therefore reductions of serum levels of inflammatory markers may be more pronounced in populations with pre-existing disease as compared to healthy individuals.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Described in an earlier publication[27], whole blood electrical impedance platelet aggregation was conducted using a Chronolog Whole Blood Lumi-Aggregometer® (Model 560VS) with reagents from Chronolog Corporation (Havertown, PA). The following agonists were tested within 2 hours of the phlebotomy: ADP at 2.5 μM, 5 μM, and 10 μM; collagen at 1 and 2 mg/ml; and arachidonic acid at 0.5 mM.…”
Section: Methodsmentioning
confidence: 99%
“…This has largely been attributed to its anti-platelet effect [6], but possibly also because of its general anti-inflammatory and pro-resolving properties from the biosynthesis of aspirin-triggered lipid mediators derived from essential fatty acids [7, 8]. Recent clinical trials have found that treatment with fish oils in combination with ASA led to significant reduction in inflammatory cytokines and that these two agents can work synergistically in lowering CVD risk [9, 10]. …”
Section: Introductionmentioning
confidence: 99%